2007
DOI: 10.1111/j.1552-6909.2006.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Persevering Through Postpartum Fatigue

Abstract: Objective:  To construct a substantive theory of postpartum fatigue. Design:  Grounded theory. Setting:  Participants were recruited in the hospital after delivery and interviewed in their homes. Participants:  Thirteen primiparae (n = 5) and multiparae (n = 8) women between 2 and 5 weeks postpartum from diverse ethnic, age, obstetric, and financial contexts were theoretically sampled. Results:  Persevering was the central human process around which the grounded theory emerged. The process of persevering was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 97 publications
1
37
0
1
Order By: Relevance
“…Our results validate fi ndings of previous research showing that postpartum fatigue in the weeks after childbirth is an overwhelming, all-consuming experience that negatively affects all aspects of the woman's life (Kennedy et al, 2007;Runquist, 2007). Family routines in the early postpartum are frequently disorganized and chaotic due to the effects that inconsistent infant her.…”
Section: Clinical Nursing Implicationssupporting
confidence: 87%
See 3 more Smart Citations
“…Our results validate fi ndings of previous research showing that postpartum fatigue in the weeks after childbirth is an overwhelming, all-consuming experience that negatively affects all aspects of the woman's life (Kennedy et al, 2007;Runquist, 2007). Family routines in the early postpartum are frequently disorganized and chaotic due to the effects that inconsistent infant her.…”
Section: Clinical Nursing Implicationssupporting
confidence: 87%
“…Interviews were semistructured using a template of questions from a prior fatigue study as a starting point (Runquist, 2007). Interviews lasted between 20 and 60 minutes with 1-month interviews typically lasting the longest and 6-month interviews the shortest, as women said they were sleeping better and had less fatigue and fatigue-related effects over time to discuss with researchers.…”
Section: Managing Fatigue After Childbirthmentioning
confidence: 99%
See 2 more Smart Citations
“…To support these women, there is a need to develop effective interventions for postpartum fatigue. (23) Studies on Pilates exercises have indicated both mental and physical effects on health. (24) For many years, Pilates exercises have been regarded as a useful tool for rehabilitation.…”
Section: Discussionmentioning
confidence: 99%